Current Stage of Entrepreneurship Development in Russia From 2014 Up To 2017: Main Issues and Trends - Sergej Smirnov; Eugeniy Cheberko (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
During the past four-year period Russian economy was markedly different from previous 2000th and early 2010th. A mix of factors including imposed economic sanctions, a growth of the public sector in the Russian economy, sufficient efforts of government agencies and Central Bank of bringing SME out of the shadow had a deep impact on different elements of the entrepreneurial ecosystem. The aim of the paper is to analyze the qualitative and quantitative changes, and explore the current trends in Russian entrepreneurship field since 2014 up to 2017. In this study, we have analyzed the latest entrepreneurial statistics and review recent researches on entrepreneurial development in Russia. To gain a more complete picture we have also considered the data of Global Entrepreneurial Monitor (GEM) and Russian entrepreneurial climate index (OPORA). A special examination was given to the informal sector's reflection in the entrepreneurial statistics. On this issue, we have collected and summarized expert opinions. Having combined information from different sources we came to the finding that despite the current negative institutional environment, despite the range of negative political factors and warning statistics of decline in the #of enterprises, the gradual development of national entrepreneurship continues. Pending the weakening of negative factors in the mid-term period we forecast that a prompt development of entrepreneurial ecosystem is highly probable in the nearest few years.
Keywords: 650; Entrepreneurial climate; Statistics of entrepreneurship; Mass entrepreneurship in Russia; Entrepreneurship and digital transformation